Vadim Sidur as dissident in the context of his letters to Karl Aymermaher - Mianowska, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper investigates Vadim Sidur’s nonconformity, reflected in his letters to an eminent German Slavicist, Professor Karl Eimermacher. This correspondence, which lasted for 15 years – from 1971 to 1986 – contains unique factual data constituting evidence of the era. As follows from the analysis, Sidur’s acts of dissidence were of various nature. Although he was not an active politician or member of the opposition, nor did he take part in mass protests, still he did not let the party members control or suppress himself and it is by using the language of art that he expressed his disagreement with the Soviet regime. This ‘solitary nonconformist,’ despite the Soviet regime’s omnipresent prohibitiveness and censorship, achieved international fame, which the correspondence under discussion proves.